Na "Cadeira da Verdade": a ação política dos padres por meio dos púlpitos em Minas Gerais regencial (Ágora Journal, 2020)
In this article, we analyze the way in which many of the parish-priests and priests expressed themselves through the press in Minas Gerais during the 1830s, many of whom were members or supporters of the different existing political groups. We also seek to highlight the speeches made by the parish priests during the electoral process, taking into account the publications of the province's periodical press. As a result, it was observed that the parish priests acted through the pulpits during their functions, legitimately designated by the Church (as parish priest) and by the State (as a public official), which had given priests a privileged position during the electoral disputes.